2014
DOI: 10.2147/cia.s56058
|View full text |Cite
|
Sign up to set email alerts
|

Sustained effect of resistance training on blood pressure and hand grip strength following a detraining period in elderly hypertensive women: a pilot study

Abstract: IntroductionHypertension is the most prevalent modifiable risk factor with a high prevalence among older adults. Exercise is a nonpharmacological treatment shown to benefit all patients with hypertension.ObjectiveThis study examined the effects of a 14-week moderate intensity resistance training program (RT) on the maintenance of blood pressure and hand grip strength during an extended detraining period in elderly hypertensive women.MethodsTwelve hypertensive sedentary elderly women completed 14 weeks of whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…However, differences between time points reveals nothing about the clinical significance of findings or error measurement. This can be confirmed by the study from Nascimento et al 2 who used an ANOVA of repeated measurements, and demonstrated a significant decline (-10 mmHg) on SBP at post-training, and detraining time points when compared with pre-training measurements in hypertensive elderly women. Nevertheless, important insights as to inter-individual variation in training response were missed by the authors.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…However, differences between time points reveals nothing about the clinical significance of findings or error measurement. This can be confirmed by the study from Nascimento et al 2 who used an ANOVA of repeated measurements, and demonstrated a significant decline (-10 mmHg) on SBP at post-training, and detraining time points when compared with pre-training measurements in hypertensive elderly women. Nevertheless, important insights as to inter-individual variation in training response were missed by the authors.…”
Section: Discussionsupporting
confidence: 54%
“…Nevertheless, important insights as to inter-individual variation in training response were missed by the authors. Furthermore, the signicant differecens between time points observed by Nascimento et al 2 might reveal little about clinical significance of the findings or error measurement.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Anxiety decreases after exercise because it facilitates the release of βendorphin and β-lipoprotein, substances that are natural painkillers and are normally produced in the brain and cause a feeling of euphoria and well-being (Farrell et al, 1987). Exercise brings permanent changes to the most basic brain monoamines (dopamine, serotonin, noradrenaline) resulting in the creation of pleasant emotions (Nabkasorn et al, 2006) . "Thermogenesis" the increase in body temperature observed during and after the exercise has a therapeutic affect and reduces muscle tension and the activity of c' motor neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Data specific to CVD patients are currently lacking. The only study that examined hypertensive women, reported that improvements on blood pressure and muscular strength induced by RE training at a moderate intensity over a 14-week period were preserved following 14 weeks of detraining [266]. Likewise, there are no published reports on the effect of detraining on oxidative stress adaptation to RE training in the context of CVDs.…”
Section: Resistance Exercise Training and Detrainingmentioning
confidence: 99%